1973
DOI: 10.1111/j.1469-8986.1973.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long Term Exposure to Tone Pulse Noise on Human Sleep

Abstract: Electrophysiological and self‐report data were obtained from 10 and 20 Ss, respectively, during 15 days of baseline, 30 days of 24‐hr per day exposure to a 660 msec, 3.5K Hz tone pulse with a 22 sec interstimulus interval (10 days each at 80, 85, and 90 dB), and during a 10‐day post‐exposure period. A self‐reported increase in difficulty falling asleep was not substantiated by objective sleep latency measures. Changes in total hours of sleep, number of awakenings, and percent time for sleep stages were of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…[26] Thirty subjects were monitored on a 24-h tone pulse for a 30-day exposure period and a 10-day post-exposure period. No significant change was found in mean heart rates at night, total body movements during the night, objective sleep latency, total hours of sleep, number of awakenings and percent time for sleep stages.…”
Section: Noise and Sleepmentioning
confidence: 99%
“…[26] Thirty subjects were monitored on a 24-h tone pulse for a 30-day exposure period and a 10-day post-exposure period. No significant change was found in mean heart rates at night, total body movements during the night, objective sleep latency, total hours of sleep, number of awakenings and percent time for sleep stages.…”
Section: Noise and Sleepmentioning
confidence: 99%
“…Highly significant decreases in sensitivity to the auditory arousing stimulus were demonstrated. Because such threshold shifts might be due either to simple habituation (14,15) or to actual decreased sensitivity resulting from nonrestorative sleep, trials with novel frequency tones were interpolated for four sUbjects. Significant threshold increases (66% of the magnitude of threshold increase to the standard 1,000 Hz tone) were found to the novel stimuli as well as the standard tone.…”
Section: Discussionmentioning
confidence: 99%
“…Sharpless and Jasper (14) presented tones to sleeping cats and found that after approximately 30 presentations they could find no change in ongoing electroencephalogram (EEG) after tone presentation. Townsend et al (15) studied the effects of 80--90 dB tones each 22 s on sleep in young adult males and found essentially no change in sleep variables. However, this may have been because of rapid habituation and the fact that the initial nights of tone presentation were not analyzed separately.…”
mentioning
confidence: 99%
“…Other indicators of noise induced sleep disturbances such as event related awakenings were, due to the high traffic density regarded as not appropriate. The evaluation of arousals was also not considered as nocturnal noise scarcely increases the number of arousals but causes a temporal re-distribution of the arousals over night instead [30].…”
Section: Discussionmentioning
confidence: 99%